2018
DOI: 10.1007/s13197-017-3008-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulation and baking conditions on the structure and development of non-enzymatic browning in biscuit models using images

Abstract: The aim of this research was to determine the effect of composition (dietary fiber = DF, fat = F, and gluten = G) and baking time on the target microstructural parameters that were observed using images of potato and wheat starch biscuits. Microstructures were studied Scanning Electron Microscope (SEM). Non-enzymatic browning (NEB) was assessed using color image analysis. Texture and moisture analysis was performed to have a better understanding of the baking process. Analysis of images revealed that the starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…As one of the four famous embroideries in China, Guangdong embroidery was listed in the first national intangible cultural heritage list in 2006 because of its unique embroidery skills and cultural characteristics. So-called Guangdong embroidery is the silk embroidery handmade in Guangdong area (Amid et al, 2018; Leiva-Valenzuela et al, 2018; Sandefur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the four famous embroideries in China, Guangdong embroidery was listed in the first national intangible cultural heritage list in 2006 because of its unique embroidery skills and cultural characteristics. So-called Guangdong embroidery is the silk embroidery handmade in Guangdong area (Amid et al, 2018; Leiva-Valenzuela et al, 2018; Sandefur et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that hardness was increased as the microwave time was prolonged and the microwave power was increased and was mainly positively correlated (p < 0.01) with the four TPHs. The texture of biscuits is mainly affected by the changes in the spatial structure of starch, protein, and moisture (43). Through the comprehensive analysis of the above sensory indicators, AW was shown to be mainly affected by microwave power and time; the texture was mainly affected by the spatial structure of starch, protein, and moisture; and color provided a comprehensive characterization of the influence of the temperature, time, AW, and reaction substrate concentration on the formation of THPs in the microwavebaked biscuit system (44).…”
Section: Discussionmentioning
confidence: 99%
“…For texture, hardness and chewiness instrumentally indicate the sensory attributes during biting and chewing, and are often used to evaluate the quality of French fries. The textural properties of food are mainly affected by the spatial structure of food components and moisture ( 43 ). The trend in the change of hardness and chewiness were consistent with moisture content with the positively correlation coefficient was −0.85 and −0.90, respectively.…”
Section: Discussionmentioning
confidence: 99%